2014
DOI: 10.1007/s12015-014-9533-0
|View full text |Cite
|
Sign up to set email alerts
|

Combining Hypoxia and Bioreactor Hydrodynamics Boosts Induced Pluripotent Stem Cell Differentiation Towards Cardiomyocytes

Abstract: Cardiomyocytes (CMs) derived from induced pluripotent stem cells (iPSCs) hold great promise for patient-specific disease modeling, drug screening and cell therapy. However, existing protocols for CM differentiation of iPSCs besides being highly dependent on the application of expensive growth factors show low reproducibility and scalability. The aim of this work was to develop a robust and scalable strategy for mass production of iPSC-derived CMs by designing a bioreactor protocol that ensures a hypoxic and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 61 publications
1
63
0
Order By: Relevance
“…These parameters include oxygen tension, hydrodynamic culture conditions, feeding and media refreshment strategy, and the development of innovative SM delivery technologies to increase the differentiation efficacy and homogeneity and minimize hPSC cell loss after differentiation induction. More recently, it has been demonstrated that optimizing the bioprocess parameters, including oxygen tension (hypoxia), and bioreactor hydrodynamics can boost mouse iPSC differentiation toward CMs [43]. However, these finding should also be validated for differentiation of hPSC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…These parameters include oxygen tension, hydrodynamic culture conditions, feeding and media refreshment strategy, and the development of innovative SM delivery technologies to increase the differentiation efficacy and homogeneity and minimize hPSC cell loss after differentiation induction. More recently, it has been demonstrated that optimizing the bioprocess parameters, including oxygen tension (hypoxia), and bioreactor hydrodynamics can boost mouse iPSC differentiation toward CMs [43]. However, these finding should also be validated for differentiation of hPSC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…This cell line was genetically modified to integrate and stably express a transgene containing puromycin‐ N ‐acetyl transferase and enhanced green fluorescent protein (eGFP) genes, both under control of the cardiac‐restricted promoter α‐myosin heavy chain (α‐MHC) [33]. miPSCs were expanded and differentiated as aggregates in fully controlled bioreactors as previously described by our group [8]. Briefly, iPSCs were inoculated in the WAVE Cellbag (GE Healthcare, Piscataway, NJ, http://www.gelifesciences.com) as single cells, at a concentration of 7 × 10 4 cell per ml, and were cultivated under defined conditions (temperature, 37°C; pO 2 , 4% O 2 ; CO 2 , 5%; surface aeration rate, 0.1 air volume per working volume per minute (vvm); rocking angle, 4°; agitation rate, 10–26 rpm; working volume, 1 liter) in differentiation medium (Iscove's modified Dulbecco's medium with GlutaMAX, supplemented with 20% [vol/vol] fetal bovine serum, 1% [vol/vol] nonessential amino acids, 1% [vol/vol] penicillin/streptomycin, and 50 μM β‐mercaptoethanol [all from Invitrogen, Carlsbad, CA, http://www.invitrogen.com]).…”
Section: Methodsmentioning
confidence: 99%
“…However, the efficiency of differentiation of human PSCs in suspension systems has been variable [201204]. Correia and colleagues differentiated human iPSCs to cardiomyocytes using the Cellbag™-WAVE bioreactor (GE Healthcare) in 4% oxygen, rather than continuous or intermittent agitation in a stirred-tank bioreactor [205]. They reported obtaining a purity of ~75% and an impressive yield of 60 cardiomyocytes per input undifferentiated cell.…”
Section: Remaining Obstacles To the Successful Translation Of Plurmentioning
confidence: 99%